2005
DOI: 10.1037/1528-3542.5.4.456
|View full text |Cite
|
Sign up to set email alerts
|

Defocused Attention in Depressed Mood: Evidence From Source Monitoring.

Abstract: The authors suggest that depressed mood is associated with a defocused mode of attention, allowing irrelevant information to be noticed and processed more than in nondepressed states. Working on a source monitoring task, subclinically depressed college students selected with the Beck Depression Inventory (A. T. Beck, 1967; D. Kammer, 1983) had better memory for irrelevant stimulus aspects than nondepressed control students. However, depressed students' performance on the relevant stimulus aspects was unimpaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 46 publications
7
60
0
1
Order By: Relevance
“…In our study (von Hecker & Meiser, 2005), 44 nondepressed and 30 depressed participants (BDIselected) had to learn 64 individual nouns that were presented individually on a computer screen, each one on either the left or the right side of the screen, and each one surrounded by either a red or green frame. Participants were told that they later would be asked to recognize these 64 words as "old" when randomly presented among 64 distractors.…”
Section: Defocused Attention In Depressionmentioning
confidence: 99%
“…In our study (von Hecker & Meiser, 2005), 44 nondepressed and 30 depressed participants (BDIselected) had to learn 64 individual nouns that were presented individually on a computer screen, each one on either the left or the right side of the screen, and each one surrounded by either a red or green frame. Participants were told that they later would be asked to recognize these 64 words as "old" when randomly presented among 64 distractors.…”
Section: Defocused Attention In Depressionmentioning
confidence: 99%
“…In contrast, there is also evidence to show that depressed individuals may sometimes attend to task-irrelevant information (von Hecker and Meiser, 2005), as they also often find it difficult to inhibit such information (Hertel, 1997(Hertel, , 1998Hertel and Rude, 1991;Joormann, 2010). Such a defocused mode of attention is sometimes regarded as reflecting an adaptive mechanism which allows for seeking new opportunities or ways of problem solving, even if these may appear irrelevant or perceptually peripheral at the time.…”
Section: Introductionmentioning
confidence: 99%
“…To examine this prediction with respect to memory performance, von Hecker and Meiser (2005) used a source monitoring paradigm that allows for separating various components of memory performance, relating to relevant and irrelevant aspects of the materials learnt. In their study participants had to learn 64 nouns that were presented individually on a computer screen, on either the left or the right side of the screen, and each surrounded by either a red or green frame.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Source monitoring deficits have also been reported in depression. Ulrich and Meiser [79] found that depressed patients when assessed with the Beck Depression Inventory [80] showed better memory for irrelevant stimuli relative to stimuli required for task performance in a source monitoring experiment. The subjects had to decide if a word was old or new, and if old, if the word had been presented on the left or the right side of the screen, and if the word had been presented inside a green frame or a red frame.…”
Section: Source-monitoringmentioning
confidence: 99%